Endoscopic Third Ventriculostomy for Obstructive Hydrocephalus and Ventriculocystostomy for Intraventricular Arachnoid Cysts - Akgun, Bekir; Ozturk, Sait; Hergunsel, Omer Batu; Erol, Fatih Serhat; Demir, Fatih (Charles University Faculty of Medicine in Hradec Kralove, 2021)
Objective: To evaluate and discuss the outcomes of a combination of ventriculocystostomy (VC) and endoscopic third ventriculostomy (ETV) for obstructive hydrocephalus (HCP) due to ventricular/cisternal arachnoid cysts, and only ETV for obstructive HCP due to different etiologies. Methods: We retrospectively reviewed all 40 symptomatic patients (aged 4 months – 61 years) of obstructive HCP treated by ETV or VC+ETV during October 2014 – April 2019. VC+ETV was performed in 7 patients with intraventricular/cisternal arachnoid cyst and obstructive HCP. Only ETV was performed in 33 patients with obstructive HCP due to other etiologies. Results: Successful ETV or VC+ETV surgery was performed in 35 patients. The procedure failed in 5 patients aged < 1 year; all these 5 patients had a head circumference (HC) of > 90 percentile at the time of surgery. Another 5 patients aged < 1 year showed successful ETV, with a HC of 75–90 percentiles. Conclusion: ETV is a successful alternative treatment for obstructive HCP. The ventricular size may not demonstrate a remarkable reduction post-ETV than post-shunting. Accordingly, increased intracranial pressure may not effectively decrease during the early period post-ETV than post-shunting. Therefore, the success rates of VC and/or ETV are low in very young patients with very high HCs (> 90 percentile). © 2021 The Authors.
Keywords: endoscope; third ventriculostomy; ventriculocystostomy